(untitled) (Global Journal of Management and Business Research, 2018)
The improvement of financial sector in Tanzania by the introduction of financial reforms was expected to improve the efficiency of the financial sector which includes lowering the Interest rate spread. Beyond the expectations of the reforms the interest rate spread is high with no sign of narrowing down. This study was set to analyse the determinants of Interest rate spread in Tanzania commercial banks focusing on the internal characteristics. Data from commercial banks incorporated before 2002 were extracted and analysed using SPSS 16 and regression model was established. The results indicate that operating costs, loan loss provisioning, and liquidity risk increases the interest rate spread. While factors of required reserve and non-interest income decrease the interest rate spread.